Financial inclusion: transforming Mozambique into a mobile money success-case - Piñera, Inês Coelho Alvarez Y (2021)
This work project aims to provide the Mozambican government with a strategic model to improve the country’s financial inclusion, and more specifically, its mobile money sector. The inability faced by banks to serve rural and impoverished populations enabled for the creation of mobile money, which is taking a rapid uptake in several Sub-Saharan African countries, providing a variety of services that significantly improve individual’s well-being. Nonetheless, Mozambique has not yet perceived the full development of this sector when compared to its neigh boring countries. Hence, the country’s mobile money sector is analyzed to understand the challenges currently faced, so that a structured approach can be in troduced to transform Mozambique into a mobile money success-case.